Kesiapan Gizi dan Kesehatan Reproduksi Calon Pengantin sebagai Faktor Pencegahan Stunting pada Anak - Noeroel Arham; Erna Fitria; Adella Safitry; Rismaliza Rismaliza; Hizqia Azzura; Ainul Riski; Sayyida Nabila; Widia Rahmatun Anja (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This report aims to identify and address the problem of stunting in prospective brides and grooms in the Piyeung Health Center area, Aceh Besar. Stunting is a serious health problem that can affect the growth and development of children. Through the counseling activities carried out, the author seeks to increase the knowledge and awareness of prospective brides and grooms regarding the importance of good nutrition before and during pregnancy to prevent stunting. The methodology used in this report is Quasy Experiment. The results of this activity indicate an increase in understanding of nutrition and reproductive health among prospective brides and grooms. The conclusion of this report emphasizes the importance of appropriate and sustainable nutritional interventions to prevent stunting, as well as the need for support from various parties to improve the quality of public health. It is hoped that this report can be a reference for related parties in efforts to prevent stunting in the future.